Juridical Review On River Pollution Due To Liquid Waste Of The Tofu Factory In Kalisari Village Based On Regional Regulation Of Banyumas Regency Number 8 Of 2018 Regarding Wastewater Management - Ratri, Wulanindra Kumala (UMPurwokerto Law Review, 2022)
Abstract Pollution is when a substance or energy is introduced into an environment by human activities or natural processes resulting in the climate not functioning correctly. Banyumas Regency is currently developing in various industrial activities, for example, the tofu industry in Kalisari Village, which causes pollution due to the entry of waste disposal that is not included in the WWTP. Based on this background, the problem formulation can be taken as a juridical review of river pollution due to tofu factory waste in Kalisari village based on Banyumas Regency Regulation Number 8 of 2018 concerning Wastewater Management and what the obstacles faced in the process of dealing. Tofu river pollution based on Regional Regulations Banyumas Regency Number 8 of 2018 concerning Wastewater Management. The research method in this study is the normative juridical method. Normative legal research is research with one type of legal research methodology whose analysis is based on applicable laws and regulations and is relevant to the legal issues that are the focus of this research. The normative juridical research method is carried out through a literature study of secondary data regarding the provisions of laws and regulations, research results, or others. Specifications The data used is descriptive. Based on the results of the analysis obtained based on the Banyumas Regency Regulation Number 8 of 2018 concerning Wastewater Management, it is stated that "everyone has the same rights in obtaining clean water, and the obstacles faced are because the pipes often come loose resulting in waste into the river. Keywords: pollution, industry, tofu liquid waste Â Abstrak Pencemaran adalah keadaan di mana suatu zat atau energi diintroduksikan ke dalam suatu lingkungan oleh kegiatan manusia atau oleh proses alam yang mengakibatkan lingkungan itu tidak berfungsi dengan baik. Kabupaten Banyumas saat ini berkembang dalam melakukan berbagai kegiatan industri contohnya industri tahu yang menyebabkan pencemaran karena masuknya sisa pembuangan limbah yang tidak masuk dalam IPAL. Berangkat dari latar belakang tersebut maka diambil rumusan masalah bagaimana tinjauan yuridis terhadap pencemaran sungai akibat limbah pabrik tahu di desa Kalisari berdasarkan Peraturan Daerah Kabupaten Banyumas Nomor 8 tahun 2018 tentang Pengelolaan Air Limbah dan apa saja kendala yang dihadapi dalam proses menangani pencemaran sungai limbah tahu berdasarkan Peraturan Daerah Kabupaten Banyumas Nomor 8 Tahun 2018 tentang Pengelolaan Air Limbah. Metode penelitian dalam penelitian ini yaitu metode yuridis normatif. Penelitian hukum normatif adalah penelitian dengan satu jenis metodologi penelitian hukum yang analisisnya didasarkan pada peraturan perundang-undangan yang berlaku dan relevan dengan permasalahan hukum yang menjadi fokus penelitian ini. Metode penelitian yuridis normatif dilakukan melalui studi pustaka terhadap data sekunder mengenai ketentuan peraturan perundang-undangan, hasil penelitian atau lainnya. Spesifikasi data yang digunakan yaitu deskriptif. Berdasarkan hasil analisis yang diperoleh yaitu berdasarkan Peraturan Daerah Peraturan Daerah Kabupaten Banyumas Nomor 8 Tahun 2018 tentang Pengelolaan Air Limbah disebutkan bahwa setiap orang memiliki hak yang sama dalam mendapatkan air bersih dan kendala yang dihadapi karena pipa sering kali terlepas dan mengakibatkan masuknya limbah ke sungai. Kata kunci: pencemaran, indutri, limbah cair tahu